Analysis of New Bone Formation Induced by Periosteal Distraction in a Rat Calvarium Model. (9th May 2011) - Saulacic, Nikola; Schaller, Benoit; Iizuka, Tateyuki; Buser, Daniel; Hug, Cladius; Bosshardt, Dieter D.
ABSTRACT Background: A controlled, gradual distraction of the periosteum is expected to result in the formation of new bone. Purpose: This study was designed to estimate the possibility of new bone formation by periosteal distraction in a rat calvarium model. Material and Methods: Sixteen animals were subjected to a 7‐day latency period and distraction rate at 0.4 mm/24 hours for 10 days. Two experimental groups with seven rats each were killed at 10 and 20 days of consolidation period and analyzed by means of microcomputed tomography, histologically and histomorphometry. Results: In the central regions underneath the disk device, signs of both bone apposition and bone resorption were observed. Peripheral to the disc, new bone was consistently observed. This new bone was up to two and three times thicker than the original bone after a 10‐ and 20‐day consolidation period, respectively. Signs of ongoing woven bone formation indicated that the stimulus for new bone formation was still present. There were no statistically significant differences regarding bone density, bone volume, and total bone height between the two groups. Conclusion: The periosteal distraction model in the rat calvarium can stimulate the formation of considerable amounts of new bone.